1960
DOI: 10.1530/acta.0.xxxv0397
|View full text |Cite
|
Sign up to set email alerts
|

Turner-Syndrom Mit Voll Ausgebildeten Sekundären Geschlechtsmerkmalen Und Fertilität

Abstract: Two women with normally developed secondary sex characteristics are reported. Both had spontaneous menstrual cycles, the first one during a period of 4 years, the second one started menstrual bleedings at the age of 17 and had menstrual cycles of regular intervals up to the present age of 39. She had given birth to a healthy boy at the age of 31. Both patients are chromatinnegative, of short stature and one has a unilateral webbed neck. Therefore they had to be classified as cases of Turner's syndrome. In cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1963
1963
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…At present, 19 pregnancies in 12 monosomy X pa tients have been reported [1,[5][6][7][8][9][10][11][12][13][14] (table 2). The stature was less than 142 cm in 10 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, 19 pregnancies in 12 monosomy X pa tients have been reported [1,[5][6][7][8][9][10][11][12][13][14] (table 2). The stature was less than 142 cm in 10 cases.…”
Section: Discussionmentioning
confidence: 99%
“…A breakdown according to chromosome constitutions showed that 21 pregnancies were from 13 patients with 45,XO [1,[5][6][7][8][9][10][11][12][13][14] [37], Pregnancy in the first case terminated spontaneously in the 3rd month. In the second, one of the twins ended as stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…1965). Fertility in a woman with 45,X Turner's syndrome was described for the first time by Bahner et al (1960). Since then, a further six cases have been reported (Schokeir 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Gonadal dysgenesis may thus be due to a rapid atresia rather than a congenital absence of germ cells in the gonads, but the cause of this atresia is unknown. Some quantitative effect may be acting, and therefore in rare cases, such as in our first case, some germ cells may remain in the ovaries, allowing the patient to have a transitory ovarian function and even to get pregnant (Bahner et al 1960;Grace et al 1973; Nakashima 8c Robinson 1971). Mosaicism is another possible explanation, but we found no evidence of mosaicism by study of five different tissues (Philip 8c Sele 1976).…”
mentioning
confidence: 89%